Identification of Metallophores and Organic Ligands in the Chemosphere of the Marine Macroalga Ulva (Chlorophyta) and at Land-Sea Interfaces - Wichard, Thomas (Frontiers in Marine Science, 2016)
The roles of organic matter in seawater have often been discussed from the aspect of metal toxicity and bioavailability in seawater. In fact, organic ligands, as part of the organic matter, can work as a trace metal ion buffer system. At the same time, however, the release of well-defined metal chelators as exudates by, for example, marine bacteria is necessary to compete with natural metal complexes and sustain the metal acquisition required for several processes including nitrogen fixation. The identification, isolation and structure elucidation of chelators is, thus, essential to our understanding of metal stress management in the natural habitat and role of these chelators on cellular process. The isolation of an organic ligand from its chemosphere is a challenging task. The purpose of this paper is, therefore, to give an additional perspective on how the effective application of stable isotope pairs of a metal of interest (both cations and oxoanions) combined with mass spectrometric analyses can pave the way to discovering new organic ligands (i.e. metallophores) and the chelating characteristics of dissolved organic matter (DOM): Pairs of isotopes, such as 54Fe and 58Fe (or any other pair of available isotopes of a given metal), can be used to create easily detectable unique isotopic signatures in mass spectra when they are bound by chelators. The identification of organic ligands is outlined for a proposed model system of mutualistic interactions between the green macroalga Ulva (Chlorophyta) and associated bacteria, as well as discussed briefly for DOM along land-sea gradients.